Implementation on Transfer of Undertaking Protection of Employment to Outsourcing Labors in Semarang Indonesia: A Legal Approach - Herlambang, Pratama Herry (Faculty of Law, Universitas Negeri Semarang, 2018)
Assurance of proper and good job is one of indicators of the success of the State to run the constitution in accordance with the mandate of the Constitution of the Republic of Indonesia. In the era of free trade and economic society, work is a problem that is less of a concern for the state because there is no comprehensive protection. Even in the year 2003 was born a law on employment, at the beginning of the law establishment, a lot of optimism that of the Indonesian population especially workers who have been unprotected related to the rights of workers. But over time, many problems arise in the community one of them is the guarantee of continued work for outsourcing workers, so a thorough legal review of employment protection guarantees is shifted to its work.